Some Important Hepatoprotective Medicinal Plants In Ayurveda- A Review - Paudel, Kiran; Ramamurthy, A; Sharma, Gaurav (International Research Journal of Ayurveda & Yoga, 2020)
The liver is the chief site of Metabolism of nutrients and energy production in the human body. Environment, pathogenic micro-organisms, viruses, drugs and chemical agents are the main factors of the many type of Liver disease. Hepatic necrosis, Hepatitis, Liver fibrosis and Liver cirrhosis etc. are the common disease found in the community related to the liver. Berberis aristata, Andrographis paniculata, Achyranthes aspera etc. plants are renowned for their satisfactory activity against certain hepatic related diseases. About 80% of the world population relies on the use of traditional medicine, which is predominantly based on plant material. The present review discusses different types of medicinal plants in Ayurveda containing hepatoprotective activity with other important activities too. Therefore, the present review is aimed to compiling data on hepatoprotective medicinal plants.